2020
DOI: 10.3389/fneur.2020.00002
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Determinants of Recurrence at 1 Year and 5 Years After Stroke in a Low-Income Population in Rural China

Abstract: Recurrent stroke is becoming an increasingly important public health issue owing to the increased risk of disability and death. However, population-based studies investigating the rate of recurrent stroke in China are rare. We explored the rate and determinants of recurrent stroke within 1 and 5 years after the initial stroke in a rural population in China. Data for stroke events were obtained from the Tianjin Brain Study, conducted between 1992 and 2016. The age-standardized rates of recurrent stroke within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 56 publications
3
31
0
1
Order By: Relevance
“…Along these lines, Han Jing et al analyzed stroke recurrence in a rural population and found rates similar to those of the ARTPER study: the recurrent stroke rate was 22.5% at five years [ 11 ]. As in other studies, diabetes was an independent risk factor [ 11 , 24 ]. The ARTPER study looked at urban patients who had easy access to the hospital and primary health center.…”
Section: Discussionsupporting
confidence: 72%
“…Along these lines, Han Jing et al analyzed stroke recurrence in a rural population and found rates similar to those of the ARTPER study: the recurrent stroke rate was 22.5% at five years [ 11 ]. As in other studies, diabetes was an independent risk factor [ 11 , 24 ]. The ARTPER study looked at urban patients who had easy access to the hospital and primary health center.…”
Section: Discussionsupporting
confidence: 72%
“…Our findings contradict several studies that have found a history of diabetes as an independent risk factor for an isolated stroke event and stroke recurrence. An HbA1c level ≥6.1% at admission is an independent predictor for stroke recurrence, and the risk of recurrent stroke increases with increasing HbA1c values [21][22][23][24][25]. In this study, we used the casual blood sugar level; however, fasting blood sugar is a better predictor of neurological outcome than casual blood sugar and HbA1c following an acute stroke event [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent stroke is a frequent complication after stroke. Han et al [7] showed that the overall age-standardized rate of recurrent stroke within one year and five years was 5.7% and 22.5%, respectively. The recurrent stroke could greatly promote the risk of disability and death [7].…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [7] showed that the overall age-standardized rate of recurrent stroke within one year and five years was 5.7% and 22.5%, respectively. The recurrent stroke could greatly promote the risk of disability and death [7]. One study indicated that stroke patients with recurrence events impacted 3 months of unfavorable functional outcomes [8], and another study confirmed that recurrent stroke had been associated with increased mortality and functional dependence [9].…”
Section: Introductionmentioning
confidence: 99%